A Case of Very-late-onset Schizophrenia-like Psychosis - Son, Ji Hyun (Korean College of Neuropsychopharmacology, 2011)
This paper presents the case of a 67-year-old woman who visited the Psychiatry Department complaining of persecutory ideas and auditory hallucinations after a buccal cancer operation. On neuropsychological testing, she demonstrated paranoid psychosis and bizarre thoughts. Hospital admission was recommended for supportive care and treatment with antipsychotics. She was initially treated with olanzapine, but this medication had little effect and was replaced with amisulpride, which reduced the residual symptoms. The aim of this report was to discuss the diagnostic process and treatment of very late-onset schizophrenia-like psychosis.